2016
DOI: 10.1038/srep26752
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in anorexia nervosa does not ameliorate the faecal microbiota, branched chain fatty acid profiles and gastrointestinal complaints

Abstract: The gut microbiota not only influences host metabolism but can also affect brain function and behaviour through the microbiota-gut-brain axis. To explore the potential role of the intestinal microbiota in anorexia nervosa (AN), we comprehensively investigated the faecal microbiota and short-chain fatty acids in these patients before (n = 55) and after weight gain (n = 44) in comparison to normal-weight participants (NW, n = 55) along with dietary intake and gastrointestinal complaints. We show profound microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
406
9
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(453 citation statements)
references
References 57 publications
(96 reference statements)
23
406
9
15
Order By: Relevance
“…During weight gain, abundance of Bacteroidetes decreased even further, whereas Firmicutes abundances increased. Actinobacteria and Verrucomicrobia abundances were also higher in AN patients, and Verrucomicrobia levels did decrease after weight gain [83]. Moreover, the AN microbiota gained significantly in diversity and richness after weight gain, although this effect may in part be diet dependent [83].…”
Section: Microbial Characteristics In Undernutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…During weight gain, abundance of Bacteroidetes decreased even further, whereas Firmicutes abundances increased. Actinobacteria and Verrucomicrobia abundances were also higher in AN patients, and Verrucomicrobia levels did decrease after weight gain [83]. Moreover, the AN microbiota gained significantly in diversity and richness after weight gain, although this effect may in part be diet dependent [83].…”
Section: Microbial Characteristics In Undernutritionmentioning
confidence: 99%
“…Mack et al [83] compared the microbial composition of AN patients before and after weight gain to normal weight controls. They found that AN patients at baseline had significantly lower levels of Bacteroidetes compared to controls.…”
Section: Microbial Characteristics In Undernutritionmentioning
confidence: 99%
“…Diminished microbial diversity may be associated with unhealthy eating patterns that can lead to the debilitating weight loss associated with AN (Alcock et al, 2014). Alterations to gut microbial profiles in AN patients persist after weight gain, although some increase in microbial richness, including elevated numbers of operational taxonomic units and increased diversity of population, is observed (Mack et al, 2016). Additionally, the presence of specific strains of gut bacteria have been linked to ED-related clinical features, e.g.…”
Section: Gut Microbiota Dysbiosis and Edsmentioning
confidence: 99%
“…Indeed, Anorexia Nervosa (AN) patients have significantly lower amounts of total intestinal bacteria and higher prevalence of specific bacterial strains, which may reflect altered metabolic capacity resulting from the disorder (Armougom et al, 2009;Morita et al, 2015;Bulik, 2016;Carr et al, 2016;Mack et al, 2016). Gut bacteria may play a role in cravings for specific foods or induce dysphoria to motivate the ingestion of foods (Alcock et al, 2014).…”
Section: Gut Microbiota Dysbiosis and Edsmentioning
confidence: 99%
“…The mucosa-colonising bacterium Akkermansia muciniphila is strongly correlated with a lean phenotype and increased barrier function (Everard et al 2013, Mack et al 2016, Reunanen et al 2015. The correlation between Akkermansia muciniphila and host might depend on an additional microbial player.…”
Section: Chaptermentioning
confidence: 99%